ACADEMIC PERFORMANCE OF THE CHILDREN WITH VISUAL AND HEARING IMPAIRMENT IN SPECIAL SCHOOLS - Kaur, Dr. Jaswinder (The journal of contemporary issues in business and government, 2019)
This study aims to look at the academic performance of Special School pupils with visual and hearing impairments. A total of 264 youngsters with visual and hearing impairments were chosen from the Jammu and Kashmir districts of Baramulla and Srinagar for this study. The findings of the study reveal that instructors in special schools assist and encourage children with special needs (CWSN) in their academics. The overall result reveals that their teachers provided the most assistance and support to the CWSN in their academic achievement in special schools.